Riding the Waves of Latent Herding Online Shopping Behaviour - Noor Azuan bt Hashim (Modern Perspectives in Economics, Business and Management Vol. 5, 2021)
The Internet has grown tremendously in the recent and many of its applications have been used by people all over the world. Online shopping which is a recent phenomenon in the field of electronic commerce (e-commerce) is definitely going to be the future of shopping in the world, particularly during and after the coronavirus disease 2019 (COVID-19) outbreak. It seems that online shopping has been one of the ways that customers shop nowadays especially to the younger generations and working people. Most of the young working people have accessed to the internet due to its ubiquitous and many have started to sell and buy online. Though online shopping is quite common now, its growth in Malaysian market is still not in line with the global market. The potential growth of online shopping has triggered the idea of conducting an exploratory study on online shopping in Malaysia. A survey was carried-out with 168 part-time students who work in Klang Valley area and also currently study in Universiti Kebangsaan Malaysia (UKM). The purpose of this study is to find out how well they understand about online shopping and what factors contribute to their online shopping behaviors. The results of study reveal that customer satisfaction, motivation and influence from other buyers are among the critical factors for customers to shop online. Respondents since to mimic other customers in buying online. The results of the study could be further used by the researchers and practitioners for conducting future studies in the similar area.